Screening and identification of potential green polylactic acid (GPLA)-degrading bacteria isolated from biofertilizer samples - Kee, Wei Xuan (2024)
Plastic pollution has emerged as a global issue that caused negative impact to the environment and human health. This has led to the development of biodegradable plastic, such as polylactic acid (PLA) to reduce the plastic hazards. Green polylactic acid (GPLA) is originated from the PLA family which is derived from renewable sources with an enhanced biodegradability. Biofertilizer is frequently used in the agricultural sector to improve plant growth and crop yields. It contains microbial agents which possess potential in plastic biodegradation. In this project, bacterial isolates from biofertilizer samples were screened for GPLA degradation using clear zone assay and identified by 16S rDNA sequencing. The bacterial isolates were incubated on M9 screening media supplemented with different composition of GPLA powder at 30°C for a week. Coomassie Brilliant Blue solution was employed to visualise the formation of clear zone. Bacterial isolates that demonstrated zone of clearance were selected to perform genomic DNA extraction using phenol chloroform method, followed by PCR amplification of the 16S rDNA encoding gene and sequence analysis. The sequencing results were compared to the database of NCBI using BLAST programme to determine the identity of the potential GPLA degraders. The results showed that two bacterial isolates were able to produce clear zone on 0.2, 0.4, and 0.6% GPLA screening plates. Based on the 16S rDNA sequence analysis, the bacterial isolates were identified as Brucella intermedia and Stenotrophomonas maltophilia strain W1-2. Further evaluation of GPLA degradation by B. intermedia and S. maltophilia is required to understand the biodegradation mechanisms. This study provided insights in the application of microorganisms in the biofertilizer for plastic waste management.